Human-Centered AI: Designing Intelligent Systems that Empower, Not Replace - Purwanto, Ahmad Nur Ihsan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of artificial intelligence (AI) has generated both optimism and concern regarding its impact on human society. While AI holds significant potential to augment human capabilities, fears of widespread automation and job displacement remain prevalent. This study explores the concept of human-centered AI, emphasizing the design of intelligent systems that empower individuals rather than replace them. Drawing on a qualitative library research approach, the paper analyzes ethical principles, including fairness, accountability, transparency, and inclusivity, as well as practical design strategies such as human-in-the-loop frameworks, explainable AI, and participatory methods. The findings highlight a persistent gap between abstract ethical ideals and their practical translation into technical systems. To bridge this gap, the study proposes integrating normative values with engineering practices through actionable design principles and interdisciplinary collaboration. The research concludes that developing human-centered AI is essential to ensuring that technological progress fosters human flourishing, equity, and social justice in an era of accelerating digital transformation.